Characterization of a newly isolated self-flocculating microalga Bracteacoccus pseudominor BERC09 and its evaluation as a candidate for a multiproduct algal biorefinery. (October 2022) - Malik, Sana; Ashraf, Muhammad Umer Farooq; Shahid, Ayesha; Javed, Muhammad Rizwan; Khan, Aqib Zafar; Usman, Muhammad; Manivannan, Arthi; Mehmood, Muhammad Aamer; Ashraf, Ghulam Abbas
Abstract: Microalgae have the highest capability to fix the atmospheric carbon and wastewater-derived nutrients to produce high-value bioproducts including lipids and carotenoids. However, their lower titers and single-product-oriented biomass processing have made the overall process expensive. Hence, increased metabolite titer and processing of the biomass for more than one product are required to ensure the commercial robustness of the algal biorefinery. In this study, a newly isolated algal strain was identified as Bracteacoccus pseudominor BERC09 through phylogenetic analysis based on the 18S rRNA gene sequence. Basic characterization of the strain revealed its promising potential to produce carotenoids and lipids. The lipids and carotenoid biosynthesis pathways of BERC09 were further triggered by manipulating the abiotic factors including nitrogen sources (NaNO3, KNO3, NH4 Cl, Urea), nitrogen concentrations (0.06–0.36 gL -1 ), light intensity (150 μmolm −2 s −1 to 300 μmolm −2 s −1 ), and light quality (white and blue). Resultantly, 300 μmolm −2 s −1 of blue light yielded 0.768 gL -1 of biomass, 8.4 mgg −1 of carotenoids, and 390 mgg −1 of lipids, and supplementation of 0.36 gL -1 of KNO3 further improved metabolism and yielded 0.814 gL -1 of biomass, 11.86 mgg −1 of carotenoids, and 424 mgg −1 of lipids. Overall, the optimal combination of light and nitrogen concurrently improved biomass, carotenoids, and lipids by 3.5-fold, 6-fold, and 4-fold than control, respectively. Besides, the excellent glycoproteins-based self-flocculation ability of the strain rendered an easier harvesting via gravity sedimentation. Hence, this biomass can be processed in a cascading fashion to use this strain as a candidate for a multiproduct biorefinery to achieve commercial robustness and environmental sustainability. Graphical abstract: Image 1 Highlights: A new self-flocculating algal strain was isolated, identified, and characterized. Basic characterization showed the promising potential of strain to produce carotenoids. A combined impact of nitrogen and light was studied on lipids and carotenoids biosynthesis. Optimal light and nitrogen concurrently improved lipids and carotenoids by 4-fold and 6-fold. Glycoprotein-based self-flocculation rendered >90% cells recovery in 90 min.